JURIDICAL ANALYSIS OF LEGISLATION RELATED TO THE CRIME OF TRADE IN HUMAN ORGANS FOR THE BENEFIT OF THE KIDNEY ORGAN TRANSPLANT (Comparative Studies Between Indonesia with Philippines) - Situmorang, Benny (Tadulako University, 2016)
In accordance with organ transplant’s evolve especially the kidneys it is necessary to rule out specific health legislation in dealing with transplantation of human body’s organs to prevent human trafficking of human organs. The approaches used is the approach of legislation and comparisons to provide an overview of the regulation of transplantation of human body’s organs in Indonesia, and to know the comparison with other countries that have specific rules on transplants. The result is that the regulations in Indonesia does not have rules on organ transplants from living non-related organ donation and found no legal protection againts the donor. Keywords: Organ transplant, kidney transplant, human trafficking, health legislation.